EXPLORING EFL STUDENTS’ SUBSTANCE ERROR ON DESCRIPTIVE ESSAY - Dian Purnama Sari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
This study reports on a research that analyzed substance errors in the writings of third semester English major, such as punctuation errors, typographic errors, dyslexic errors, and confusable. The technique used to collect data is a documentary technique and then the data were analyzed by using a descriptive qualitative method. By detecting punctuation errors through the four types of errors proposed by James (2013), educators can see the difficulties experienced by students and help overcome these obstacles by choosing strategies and innovative teaching methods that are appropriate to solve the problems of spelling errors faced by students. It was found that the most mistakes made by students were punctuation errors, while the least common was dyslexia. The results of this study are then recommended as input to make it easier for Indonesian learners to understand the target language, which in this study is English, especially in improving writing skill.